1997
DOI: 10.1074/jbc.272.23.14638
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intracellular Tyrosine Residue Mutation and Carboxyl Terminus Truncation on Signal Transduction and Internalization of the Rat Bradykinin B2 Receptor

Abstract: Presently, little is known of the amino acid motif(s) participating in bradykinin B2 receptor-mediated signal transduction processes. In this report we investigate the potential role of the two existing tyrosine (Tyr) residues in the intracellular regions and the carboxyl terminus in the regulatory function of this receptor. Rat-1 cells, which do not contain detectable bradykinin B2 receptor, were transfected with wild type and mutant receptor cDNAs. Tyr-131 and Tyr-321 were each mutated to corresponding alani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
1
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(90 citation statements)
references
References 22 publications
2
85
1
2
Order By: Relevance
“…These observations are in agreement with those of Faussner et al (7) who reported that truncations either at Gly 327 or Lys 315 diminished the capacity to internalize BK but left the capacity to activate PLC unchanged. These and our results are, however, inconsistent with a recent report (39) claiming compromised ligand internalization associated with reduced PLC activity for a rat B 2 receptor mutant devoid of the terminal 34 residues (corresponding to tR331 for the human receptor). Differences in species (rat versus man) and expression systems (Rat-1 versus COS-7, CHO-K1, and HEK 293) may help explain some of the observed discrepancies.…”
Section: Internalization Of [contrasting
confidence: 57%
See 1 more Smart Citation
“…These observations are in agreement with those of Faussner et al (7) who reported that truncations either at Gly 327 or Lys 315 diminished the capacity to internalize BK but left the capacity to activate PLC unchanged. These and our results are, however, inconsistent with a recent report (39) claiming compromised ligand internalization associated with reduced PLC activity for a rat B 2 receptor mutant devoid of the terminal 34 residues (corresponding to tR331 for the human receptor). Differences in species (rat versus man) and expression systems (Rat-1 versus COS-7, CHO-K1, and HEK 293) may help explain some of the observed discrepancies.…”
Section: Internalization Of [contrasting
confidence: 57%
“…This contrasts with the findings that the human ␤ 2 -adrenergic receptor truncated at position 365 was internalized to a greater extent than the wild type receptor in these cells (14). Our data show that the COOH-terminal tail contributes significantly to the internalization of the B 2 wt, although other structures such as the intracellular loops may also be involved, albeit with a reduced efficiency (39).…”
Section: Internalization Of [mentioning
confidence: 90%
“…Depending on the particular GPCR, these activities include G protein coupling (3-7), selectivity of G protein isotype (11, 11-14, 45), and homologous desensitization or internalization (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Whereas truncation of some GPCRs has been shown to modify any one or more of its functions, shortening of the COOH terminus of other family members has no apparent effects (8 -10).…”
Section: Discussionmentioning
confidence: 99%
“…Work on the ␤-adrenergic receptor, in particular, has indicated that one mechanism of desensitization involves the rapid internalization of membrane-bound receptors following agonist stimulation (15). Removal of the COOH-terminal tail of some GPCRs has been shown to greatly reduce agonist-induced internalization of the receptor while having little or no effect on signal transduction (21)(22)(23)(24)(25).…”
Section: Oxytocin (Ot)mentioning
confidence: 99%
“…В последнее десятилетие в рецепторах кининов были идентифицированы аминокислотные остатки, важные для взаимодействия с G-белком и дальнейшей передачи сигнала. Было показано, что усечение С-концевой последовательности в Б 2 Р человека вплоть до Ser 316 ослабляет, но полностью не тормозит сопряжение рецептора с Ga q -белком [74][75][76]. С другой стороны, усечение выше этого аминокислотного остатка полностью уничтожает активность Б 2 Р, что возможно приводит к разрыву a-cпирали (a8), включающей аминокислотные остатки 310 -321, которая, по-видимому, требуется для эффективного сопряжения рецептора с Ga q -белком (рис.…”
Section: 4unclassified